2018
DOI: 10.1097/cmr.0000000000000461
|View full text |Cite
|
Sign up to set email alerts
|

High baseline neutrophil-to-lymphocyte ratio predicts worse outcome in patients with metastatic BRAF-positive melanoma treated with BRAF and MEK inhibitors

Abstract: Neutrophil-to-lymphocyte ratio (NLR) has been shown to be prognostic in several solid malignancies. There are limited data regarding its value during novel therapies in patients with melanoma. The aim of the study was to assess the practical utility of this ratio in patients with BRAF-mutant melanoma treated with a combination of BRAF and MEK inhibitors (BRAFi/MEKi). We included 215 patients with inoperable or metastatic melanoma who underwent BRAFi/MEKi treatment between October 2015 and June 2017. Baseline N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
0
5
1
Order By: Relevance
“…Other parameters (PLR, LMR and SII) and their association with survival are less well studied, particularly in melanoma [29][30][31] , and even fewer data are available regarding the usefulness of these ratios in metastatic melanoma patients treated with BRAF/MEK inhibitors, where again most information pertains to the NLR (ref. [32][33][34] ). Our study confirmed the anticipated results for NLR and provided similar data for the rest of the blood cell count-derived ratios, where values above the cut-off for NLR, PLR and SII predicted reductions in OS and in PFS (ref.…”
Section: Discussionmentioning
confidence: 99%
“…Other parameters (PLR, LMR and SII) and their association with survival are less well studied, particularly in melanoma [29][30][31] , and even fewer data are available regarding the usefulness of these ratios in metastatic melanoma patients treated with BRAF/MEK inhibitors, where again most information pertains to the NLR (ref. [32][33][34] ). Our study confirmed the anticipated results for NLR and provided similar data for the rest of the blood cell count-derived ratios, where values above the cut-off for NLR, PLR and SII predicted reductions in OS and in PFS (ref.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, NLR holds the potential to predict the success of treatment prior to initiation and then again after therapy has started. Of particular interest would be utilizing NLR as a continuous variable in assessing risk of treatment failure [ 60 , 63 ]. Ideally, NLR along with other known predictors of melanoma survival could be combined into a nomogram to help predict survival while on a given therapy.…”
Section: Metastatic Melanomamentioning
confidence: 99%
“…Perhaps the most cutting-edge use of NLR in melanoma patients is in predicting, which patients will respond to targeted therapies [57][58][59]. Teterycz et al investigated 215 patients with metastatic or inoperable BRAF-positive melanoma that were treated with combination BRAF and MEK inhibitors, either dabrafenib with trametinib or vemurafenib with cobimetinib [58,60]. They determined that an NLR of greater than 4 was independently associated with diminished progression-free survival.…”
Section: Metastatic Melanomamentioning
confidence: 99%
“…Previous reports have suggested that the NLR and SII may be able to predict survival outcomes in patients with these malignancies as well. A higher NLR was suggested to be a marker of poorer overall survival (OS) and progression-free survival (PFS) in patients with metastatic RCC or melanoma 10 , 11 with a similar trend seen between higher SII values and survival outcomes in these patients. 12 , 13 It is well known how important inflammation is in the process of cancer development, and these markers are thought to be an indication of the body’s inflammatory status and thus have been investigated as indicators of prognosis.…”
Section: Introductionmentioning
confidence: 90%